2017
DOI: 10.24170/12-3-1716
|View full text |Cite
|
Sign up to set email alerts
|

Screening for asymptomatic rheumatic heart disease: Understanding the mechanisms key to the diagnostic criteria

Abstract: SCREENING FOR RHEUMATIC HEART DISEASEThe burden of rheumatic heart disease (RHD) remains unacceptably high in the third world, including Sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…These terms are synonymous and generate the so-called AMVL 'pseudoprolapse' which cannot be regarded as true prolapse, as the AMVL is seen to be in its normal position at end-systole and does not cross the annular plane. 16 Pseudoprolapse of the AMVL generates the characteristic posteriorly directed jet of rheumatic MR with a similar broad Doppler jet exhibited on the optimised PSSAX view (online supplemental clips 5-7).…”
Section: Restricted Leaflet Motionmentioning
confidence: 94%
“…These terms are synonymous and generate the so-called AMVL 'pseudoprolapse' which cannot be regarded as true prolapse, as the AMVL is seen to be in its normal position at end-systole and does not cross the annular plane. 16 Pseudoprolapse of the AMVL generates the characteristic posteriorly directed jet of rheumatic MR with a similar broad Doppler jet exhibited on the optimised PSSAX view (online supplemental clips 5-7).…”
Section: Restricted Leaflet Motionmentioning
confidence: 94%
“…Although echocardiography is presently the most discriminating tool, a deeper understanding of the disease mechanisms that underlie morphological changes will no doubt facilitate a more rational diagnostic criteria. [68]…”
Section: Problems With Echocardiographic Screening For Rheumatic Hearmentioning
confidence: 99%
“…It is, however, unclear at this stage that the group with isolated morphological change is insignificant and can be ignored. [68] The original WHO Doppler-only criteria were derived from criteria designed to diagnose acute rheumatic carditis during episodes of ARF by differentiating functional from pathological regurgitation and ignored morphological valvular changes that characterize more chronic rheumatic cardiac involvement. [357980] Marijon et al .…”
Section: Problems With Echocardiographic Screening For Rheumatic Hearmentioning
confidence: 99%
“…However, the criteria are potentially weakened by the incorporation of a non-specific Doppler-based evaluation of regurgitant valvular lesions that could erroneously include cases with ‘congenital MR’ into the ‘borderline RHD’ group ( 4 , 5 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale RHD screening program in both high- and low-risk RHD communities in the Western Cape, South Africa (unpublished data from the Echo in Africa (EIA) program) has identified that a normal variant of the posterior mitral valve leaflet (PMVL) – so-called ‘prominent posterior leaflet inter-scallop separation’ ( 5 ) – may be responsible for a proportion of screened cases identified as ‘borderline RHD’ with isolated WHF ‘pathological’ MR.…”
Section: Introductionmentioning
confidence: 99%